Distribución espacial del Guarango (Caesalpinia spinosa) en la provincia de Cotopaxi. - Cuchipe Cuchipe, Edwin Medardo (2022)
Guarango (Caesalpinia spinosa) is a tree that grows in the dry Andean forests and is known by the communities of the central highlands of Ecuador for its enormous benefits such as fixing nitrogen and restoring degraded soils. In this research, the spatial distribution of guarango in the province of Cotopaxi was determined. The characterization of the guarango tree was based on the variables height, breast height diameter, crown diameter, phytosanitary status, and month of flowering and fruiting, variables that were analyzed by descriptive statistics. The distribution and concentration of guarango in the different sectors, parishes and cantons of the province was also evaluated. The results show that the tree is distributed in the cantons of Salcedo, Latacunga and Pujili. However, the highest concentration of guarango trees is found in Salcedo canton, Panzaleo parish, and in Jacho sector. The guarango in Cotopaxi province has an average height of 4 ± 1.82 m; the diameter at breast height is 0.28 ± 0.23 m; crown diameter is 3 ± 1.71 m. They are found in ravines, along roadsides and also on borders, they are resistant to pests and diseases, flowering occurs in the months of October to November (first period) and from April to May (second period) and fruiting in the months of January to February (first period) and July to August (second period). It was determined that the tree populations are small because the conditions in which they are found are not favorable for their good development, where there is no agronomic management: lack of timely fertilization, weeding, irrigation, phytosanitary applications and pruning.